Crepe Bandages Effluent Treatment Using C.Vulgaris and Nanomaterial (Indian Journal of Engineering and Materials Sciences (IJEMS), 2023)
Increased anthropogenic activities had led to greater contamination of waterbodies which had resulted in paucity of water and depletion of water resources. Production in industries such as crepe cotton bandage processing factories has tremendously increased following COVID19 pandemic due to an unprecedented use of personal protective equipment’s and surgical cottons and bandages. The effluent from such industries releases Chemical Oxygen Demand in range of 10 -15 g/L, Ammonia of 150 mg/L and pH > 10. Treatment of such effluents in an effective and economical way reduces water demand on natural sources and water reuse. In this study, photocatalysts such as TiO2 , ZnO, ACTiO2, AgZnO were found to be effective in Chemical Oxygen Demand reduction of real effluent by 37.8 ± 2.41%, 41.79 ± 2.44%, 39.92 ± 2.4%, and 68.94 ± 2.19% under visible light set up within 4hrs of incubation period. Biological systems, on the other hand consumes organic compounds as a source of carbon and energy. Microalgae, Chlorella vulgaris was found to remove 92.94% of Chemical Oxygen Demand within 5 days with simultaneous reduction in ammonia, nitrogen, and phosphate. The results show the efficiency of the photocatalysis and microalgae-based system to remove organic and inorganic pollutants from wastewater. A combined photocatalytic pre or post treatment to a biological system will allow to meet regulatory discharge standards.